Comments on “Dynamics of Income Distribution” - Liutang Gong (Canadian Journal of Economics, 2003)
Using the Ramsey-Cass-Koopmans model with heterogeneous agents, this note presents the explicit relationship between the individual's asset holding and the aggregate capital stock. With the aid of this relationship, is examined the dynamics of income distribution as the economy expands. Finally, some examples are presented, contrary to the conjecture made in Li, Xie, and Zou (2000), showing that the income can still improve over time, even when the aggregate production function is convex.